PINK : maandblad van de NVIH COC-afdeling Nijmegen. (Nijmegen : NVIH COC-afdeling Nijmegen, 1988)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : In de Betouwstraat 9, 6511 GA Nijmegen
Nederlands
Periodiek